The roles of government organizations and key stakeholders toward a sustainable food tourism development of chinese tourist target :case study of Phuket municipality - Putsadee Sanitprem (Prince of Songkla University, 2023)
Thesis (M.A., Chinese Studies (International Program))--Prince of Songkla University, 2019